2017
DOI: 10.1016/j.chest.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statins on COPD

Abstract: PROSPERO: CRD42017060594; https://www.crd.york.ac.uk/PROSPERO/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 40 publications
0
20
0
2
Order By: Relevance
“… 91 Analysis of data from the Multi-ethnic Study of Atherosclerosis lung study, 95 coupled with evidence from experimental studies, 96 indicates that ACE-inhibitors may have a role in limiting emphysema progression and lung function decline in patients whose COPD is characterized by endothelial dysfunction, 97 and a recent meta-analysis of 10 trials which examined the clinical efficacy of statin therapy in COPD concluded that statins may well benefit COPD patients with overt CVD. 98 …”
Section: Clinical Implicationmentioning
confidence: 99%
“… 91 Analysis of data from the Multi-ethnic Study of Atherosclerosis lung study, 95 coupled with evidence from experimental studies, 96 indicates that ACE-inhibitors may have a role in limiting emphysema progression and lung function decline in patients whose COPD is characterized by endothelial dysfunction, 97 and a recent meta-analysis of 10 trials which examined the clinical efficacy of statin therapy in COPD concluded that statins may well benefit COPD patients with overt CVD. 98 …”
Section: Clinical Implicationmentioning
confidence: 99%
“…Lastly, statins – commonly used in patients with CAD – may be helpful in treating coexisting COPD. 34 …”
Section: Discussionmentioning
confidence: 99%
“…A subsequent meta‐analysis of statins in COPD demonstrated that exercise capacity, lung function and quality of life were significantly improved in comparison to placebo, and patients with CVD were more likely to benefit . At present, the evidence does not support prescribing statins for COPD in the absence of standard indications; however, statins remain underprescribed in patients with COPD.…”
Section: Managementmentioning
confidence: 99%